2023
DOI: 10.1038/s41598-023-38949-2
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the benefits of inoculated cowpeas under different climatic conditions in Namibia

Abstract: Cowpeas (Vigna uniculata L. Walp) are grown by many smallholder farmers in sub-Saharan Africa for food and their ability to fix nitrogen even under stress. Their performance depends on the indigenous rhizobial strains that live in symbiotic association with the roots; it can be enhanced if the seeds are inoculated with more effective ones. Data of the effectiveness of the technique under a variety of climatic conditions is rare. Here, we thus use a model to upscale two field experiments conducted in Namibia to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 40 publications
0
1
0
Order By: Relevance
“…Different researchers reported that rhizobia inoculation increased the yield in some studies on different species [23,26]. In an experiment conducted in Namibia under different climatic conditions in cowpea yields improved on average by 47% [46]. In the same way, in our study, cowpea var 'Cubanita 666' yields increased around 62% when Rhizobium (Fertiriz) was combined with 50% of mineral fertilizer NPK (in chambers assay), and 47% using only the biofertilizer (in the field), compared with the non-inoculated treatment.…”
Section: Discussionmentioning
confidence: 95%
“…Different researchers reported that rhizobia inoculation increased the yield in some studies on different species [23,26]. In an experiment conducted in Namibia under different climatic conditions in cowpea yields improved on average by 47% [46]. In the same way, in our study, cowpea var 'Cubanita 666' yields increased around 62% when Rhizobium (Fertiriz) was combined with 50% of mineral fertilizer NPK (in chambers assay), and 47% using only the biofertilizer (in the field), compared with the non-inoculated treatment.…”
Section: Discussionmentioning
confidence: 95%